(untitled) (Journal of Economic Research & Business Administration, 2018)
This article describes the experience of foreign countries on energy consumption, energy intensity and energy efficiency. The rating of countries on energy efficiency is given. The indicators influencing the measurement of energy efficiency are presented. Indicators of energy efficiency by sectors of the economy are given. There is a mechanism for implementing energy efficiency in Kazakhstan for various sectors of the economy: the energy sector, the industrial sector, the housing and communal services sector, and the transport sector. The statistical data of the main indicators of energy efficiency, energy intensity and energy consumption are given. The main measures of administrative and economic regulation and promotion of energy saving are considered: control over the use of energy resources, provision of tax benefits, state subsidies and subsidies for energy saving, provision of concessional lending and guarantees, introduction of a flexible tariff system, use of renewable energy sources, programs, aimed at ppopularization of energy saving among the population.